Plastic Waste : A Journey Down the Indus River Basin in Pakistan - World Bank (Washington, DC, 2022)
The perennial presence of plastic waste in the Indus River and its tributaries is a recent addition to the already extensive list of threats to water quality, ecological health, and environmental sustainability in Pakistan. While there is some information available, although insufficient, both on surface water resources as well as on solid waste management (SWM) in Pakistan, the intersection of the two remains grossly under-studied in research circles and underrepresented on policy forums. This study delineates the interface between land based plastic waste and the Indus River system with the objective of raising plastics-in-rivers as a major policy and developmental issue, and providing a starting point for researchers, policy makers, and development and environmental professionals to expand the agenda of SWM to include protection of rivers. It is the first study of its kind in Pakistan and uses a combination of active sampling of floating waste at key sites in the Indus River system, passive sampling of waste dumped along the banks at those sites, consultations with key stakeholders in the sector, and a review of relevant policies, laws, and literature.